Functional role of PLD1 signalosome in Tauopathies. (20th December 2022) - Natarajan, Chandramouli; Phan, Phu Cuong; Thomson, Bernadette; Krishnan, Balaji
Abstract: Background: Phospholipase D (PLD), a lipolytic enzyme for membrane phospholipids, exists in two isoforms of mammalian phosphatidyl choline (PC) specific PLD, inducible PC‐PLD1 and constitutive PC‐PLD2. Elevated PLD activity is well documented in clinical studies involving Alzheimer's disease (AD). Our lab was the first to show elevated PLD1 facilitates synaptic dysfunction and underlying memory deficits driven by amyloidogenic insults by Aß/tau. We observed preservation of memory in response to PLD1 specific small molecule inhibitor in transgenic mouse models and documented preservation of dendritic spines as a underlying basis. In this study, we explored a role for PLD1 in Frontotemporal Dementia in an attempt to explore its pathological role in this tauopathy‐driven dementia. Method: We studied altered expression/activity of key F‐actin signaling elements common to PLD1 signalosome in synaptosomal fractions of human post‐mortem FTD brain regions. Synaptic deficits associated with elevated PLD1 expression in human FTD samples was studied by Fluorescence Analysis of Single Synapse Long Term Potentiation (FASS‐LTP). Using immunofluorescence, we studied the association of PLD1 with tau, presynaptic and post‐synaptic receptors, and neuroinflammation markers. Result: Elevated PLD1 expression in synaptosomal fractions of post‐mortem FTD brain tissues was corroborated by synaptic deficits and association of PLD1 with postsynaptic density protein (PSD95). FASS‐LTP assay indicated relatively lower long‐term potentiation in synaptosomal fractions of FTD brains as compared to the control brains implying synaptic deficits in FTD subjects. Conclusion: In the light of these observations, we conclude elevated PLD1 expression is associated with toxicity of tau causing memory deficits in FTD patients. This PLD1‐tau interaction alters PLD signaling partners such as mTOR (mammalian target of rapamycin), cofilin and phosphocofilin. This would implicate the actin‐dependent remodeling of synapse to be a key step in the role of PLD1 signalosome in FTD. Delineating the effects of PLD1 signalosome in tauopathies such as FTD will hugely be beneficial in tau‐targeting therapeutics for a multipronged approach in the treatment of neurodegenerative disorders.